Composite silicon-carbon material, preparation method and application thereof, and lithium ion battery

By adopting a composite silicon-carbon material with a sandwich structure and using the sandwich structure of graphene nanoribbons and silicon layers, the problem that silicon-carbon negative electrode materials in the prior art cannot take into account excellent performance, and the high-rate performance, excellent first-time Coulomb efficiency and good cycle performance of lithium-ion batteries are achieved.

CN119517970APending Publication Date: 2025-02-25NINGBO SHANSHAN NEW MATERIAL TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411767123.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

When existing silicon-carbon anode materials are used in lithium-ion batteries, they cannot take into account excellent first-time Coulomb efficiency, cycle performance and rate performance.

Method used

A composite silicon-carbon material with a sandwich structure includes a graphene nanoribbon coated with a silicon layer and a graphene layer in sequence, and silicon is deposited by atomic layer deposition method, and humic acid coating and carbonization are carried out on the graphene layer to form a graphene layer.

Benefits of technology

The composite silicon carbon material has good conductivity and mechanical properties, which can effectively improve the volume expansion defect of silicon. The resulting lithium-ion battery takes into account excellent rate performance, first-time Coulomb efficiency, capacity performance and cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517970A_ABST
    Figure CN119517970A_ABST
Patent Text Reader

Abstract

The invention discloses a composite silicon-carbon material, a preparation method and application thereof and a lithium ion battery. The composite silicon carbon material comprises a sandwich structure, and the sandwich structure comprises a graphene nanobelt coated with a silicon layer and a graphene layer in sequence. The composite silicon-carbon material has good conductivity and good mechanical properties, and the lithium ion battery containing the composite silicon-carbon material can give consideration to excellent initial coulombic efficiency, cycle performance and rate capability, and has good capacity performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite silicon-carbon material and a preparation method, application and a lithium ion battery thereof. Background Art

[0002] With the rapid development of market demand for lithium-ion batteries in the past, lithium-ion batteries are considered to be the most important power source in mobile electronic devices, and their energy density increases by 7-10% every year. The demand for weight reduction, life extension and improved capacity continues to increase. However, the traditional graphite anode is approaching its theoretical capacity limit. In this regard, silicon has been considered as a viable alternative for the next generation of lithium-ion battery anode materials, with a higher theoretical specific capacity of 3589 mAh / g. However, poor conductivity and large volume expansion (over 300%) during charge and discharge usually lead to pulverization of the electrode, showing poor first coulombic efficiency, cycle performance and rate performance.

[0003] In order to use silicon as a negative electrode to counteract volume expansion and control the repeated formation of the solid electrolyte interphase (SEI) to achieve high first-time efficiency, some advanced nanomaterial design strategies have been demonstrated as an academic study. For example, the construction of a composite system of silicon and nanocarbon materials, from the nanoscale changes of silicon materials to the construction of various three-dimensional structures of silicon-carbon nanostructures, such as core-shell structure / yolk / pomegranate structure construction, the results all show that the modification effect of silicon materials from a three-dimensional perspective is the best.

[0004] Chinese patent application CN118398782 introduces a SiOC composite negative electrode material and a preparation method thereof, wherein the material comprises a SiOC composite material self-assembled by boric acid, and a layer of polymer is coated on the surface. During the continuous lithiation process, the polymer layer will expand and contract due to the change of molecular configuration, providing a controllable space for the volume expansion of the internal SiOC material, thereby improving the first cycle coulombic efficiency and cycle performance, but this improvement method is limited, and the resulting lithium-ion battery cannot take into account excellent first cycle coulombic efficiency, cycle performance and rate performance. Summary of the invention

[0005] In order to solve the problem that lithium-ion batteries obtained from existing silicon-carbon negative electrode materials cannot take into account excellent first coulombic efficiency, cycle performance and rate performance, the present invention provides a composite silicon-carbon material and its preparation method, application and lithium-ion battery. The composite silicon-carbon material has good electrical conductivity and good mechanical properties, and the lithium-ion battery containing it can take into account excellent rate performance, first efficiency and cycle performance, and has good capacity performance.

[0006] To achieve the above objectives, the present invention adopts the following technical solutions.

[0007] The present invention provides a composite silicon-carbon material, which comprises a sandwich structure. The sandwich structure comprises a graphene nanoribbon which is sequentially coated with a silicon layer and a graphene layer.

[0008] In the present invention, the graphene nanoribbon is obtained by further opening the graphene chain, and is graphene with defects in the six-membered carbon ring at the edge.

[0009] In the present invention, the mass ratio of the graphene nanoribbon to the silicon layer is preferably (1-3):1, for example, 1.7:1.

[0010] In the present invention, the mass ratio of the graphene layer to the silicon layer is preferably 1:(1-3), for example, 1:2.

[0011] In the present invention, the graphene nanoribbon preferably includes two-dimensional graphene nanoribbon and / or three-dimensional graphene nanoribbon, for example, three-dimensional graphene nanoribbon.

[0012] Wherein, the three-dimensional graphene nanoribbon is preferably a functionalized three-dimensional graphene; the functionalized three-dimensional graphene nanoribbon is, for example, an alkylated three-dimensional graphene nanoribbon.

[0013] In the present invention, the silicon content of the composite silicon-carbon material is preferably 25%-35%, more preferably 28%-33%, for example, 28.9%, 29.6%, 29.8%, 30.4%, 30.5%, 31.8%, 30.8%, 32.4% or 32.7%.

[0014] In the present invention, the carbon content of the composite silicon-carbon material is preferably 60%-70%, more preferably 63%-69%, for example, 63.7%, 63.8%, 64.2%, 64.9%, 65.7%, 66.5%, 66.7%, 67.2% or 68.2%.

[0015] In the present invention, the oxygen content of the composite silicon-carbon material is preferably 2%-5%, more preferably 2.3%-4.7%, for example, 2.3%, 2.5%, 2.7%, 3.1%, 3.2%, 3.9%, 4.4% or 4.7%.

[0016] In the present invention, the Dv50 particle size of the composite silicon-carbon material is preferably 250-400 nm, more preferably 288-352 nm, for example, 288 nm, 298 nm, 306 nm, 312 nm, 327 nm, 330 nm, 331 nm or 352 nm.

[0017] In the present invention, the electrical conductivity of the composite silicon-carbon material is preferably (0.8-2.5)×10 3 S / m, more preferably (1.9-2.5)×10 3S / m, for example, is 0.879×10 3 S / m, 1.897×10 3 S / m, 1.985×10 3 S / m, 2.089×10 3 S / m, 2.112×10 3 S / m, 2.217×10 3 S / m, 2.314×10 3 S / m, 2.417×10 3 S / m or 2.451×10 3 S / m.

[0018] In the present invention, the pore size of the composite silicon-carbon material is preferably 15-25 nm, more preferably 18-22 nm, for example, 18.7 nm, 18.9 nm, 19.3 nm, 19.7 nm, 20.8 nm, 21.7 nm or 21.8 nm.

[0019] In the present invention, the charge transfer internal resistance of the composite silicon-carbon material is preferably 35-70 Ω, more preferably 35-50 Ω, further preferably 38-46 Ω, for example, 38.9 Ω, 39.7 Ω, 41.2 Ω, 42.8 Ω, 43.9 Ω, 44.7 Ω, 45.1 Ω or 67.8 Ω.

[0020] The present invention provides a method for preparing a composite silicon-carbon material, which comprises the following steps:

[0021] S1, depositing silicon on the graphene nanoribbon to obtain a silicon-carbon precursor;

[0022] S2. Coating a graphene layer on the silicon-carbon precursor.

[0023] In step S1, the graphene nanoribbon preferably includes three-dimensional graphene nanoribbon and / or two-dimensional graphene nanoribbon, for example, three-dimensional graphene nanoribbon.

[0024] Wherein, the pore size of the three-dimensional graphene nanoribbon is preferably 13.6-19.8 nm, for example, 16.8 nm.

[0025] Wherein, the Dv50 particle size of the three-dimensional graphene nanoribbon is preferably 150-280 nm, for example, 200 nm.

[0026] The three-dimensional graphene nanoribbon is preferably a functionalized three-dimensional graphene nanoribbon, and the functionalized three-dimensional graphene nanoribbon is, for example, an alkylated three-dimensional graphene nanoribbon.

[0027] Wherein, the preparation method of the three-dimensional graphene nanoribbon preferably comprises the following steps:

[0028] The mixture of carbon nanotubes, stabilizers and chain openers is subjected to a first reaction to obtain a reaction material; the reaction material is washed and dried to obtain the carbon nanotubes, wherein the carbon nanotubes include multi-walled carbon nanotubes.

[0029] Preferably, the content of the multi-walled carbon nanotubes is greater than 50%, where the percentage is the mass percentage of the carbon nanotubes.

[0030] Preferably, the carbon nanotubes further include single-walled carbon nanotubes.

[0031] Preferably, the stabilizer is 1,2-dimethoxyethane.

[0032] Preferably, the chain opening agent is a Na / K alloy.

[0033] Preferably, after obtaining the reaction material, the method further comprises adding the reaction material to a functionalizing agent to carry out a second reaction; wherein the functionalizing agent is preferably a halogenated alkane; further preferably, the halogenated alkane is an iodinated alkane, such as 1-iodinated alkane.

[0034] In some more preferred embodiments, the number of C atoms in the 1-iodoalkane is between 5 and 16; the 1-iodoalkane is, for example, 1-iododecane.

[0035] Preferably, the washing reagent is one or more of methanol, tetrahydrofuran, polyacrylate, water and ether.

[0036] Preferably, the method for preparing the mixture comprises the following steps: adding a stabilizer to the multi-walled carbon nanotubes, and then adding a chain opener.

[0037] Preferably, the preparation of the three-dimensional graphene nanoribbons is carried out in a glove box.

[0038] In some preferred embodiments, the drying is freeze drying, CO2 supercritical drying or vacuum drying.

[0039] The freeze-drying temperature is preferably between -30°C and -80°C.

[0040] Wherein, the freeze-drying time is preferably 3-7h.

[0041] Wherein, the temperature of the CO2 supercritical drying is preferably 10-40°C.

[0042] Wherein, the pressure of the CO2 supercritical drying is preferably 10-15 kPa.

[0043] Wherein, the CO2 supercritical drying time is preferably 1-3h.

[0044] Wherein, the vacuum drying temperature is preferably 80-100°C.

[0045] Wherein, the vacuum drying time is preferably 10-24 h.

[0046] In step S1, the method of depositing silicon is preferably an atomic layer deposition method; the atomic layer deposition method comprises the following steps:

[0047] Atomic layer deposition is performed on the graphene nanoribbon using silicon source gas.

[0048] Preferably, the silicon source gas is silane; the silane preferably includes one or more of tetraethoxysilane, methylsilane and ethylsilane.

[0049] Preferably, the flow rate of the silicon source gas is 50-100 mL / min, for example, 80 mL / min.

[0050] Preferably, the working temperature of the atomic layer deposition is 200-400°C, for example, 350°C.

[0051] Preferably, the atomic layer deposition process lasts for 32-48 hours, for example, 40 hours.

[0052] Preferably, the number of cycles of the atomic layer deposition is 200-400 times, for example, 230 times.

[0053] Wherein, after the atomic layer deposition, it is preferred that the process further includes the steps of purging with an inert gas and cooling.

[0054] The cooling rate of the cooling is preferably 10-30°C / min, for example 15°C / min.

[0055] In step S2, the method of coating the silicon-carbon precursor with a graphene layer preferably comprises the following steps:

[0056] S2-1, heating the premix to remove the solvent, thereby obtaining a humic acid-coated silicon-carbon precursor, wherein the premix comprises the silicon precursor, humic acid and a solvent;

[0057] S2-2, sintering the humic acid-coated precursor;

[0058] S2-3, carbonization, graphene layer is formed in situ after thermal decomposition of humic acid.

[0059] In step S2-1, the humic acid is preferably humic acid powder.

[0060] In step S2-1, the mass ratio of the silicon-carbon precursor to the humic acid is preferably (80-90):(20-30), for example, 85:25.

[0061] In step S2-1, the solid-liquid ratio of the premix is ​​preferably 1:(10-15), for example, 1:12.

[0062] In step S2-1, the method for preparing the premix preferably comprises: adding the silicon-carbon precursor and humic acid into water, mixing them, and adding an ammonia solution under stirring conditions.

[0063] The mass concentration of the ammonia solution is preferably 10%-30%, for example 28%.

[0064] The method of adding the aqueous ammonia solution is preferably dropwise addition. Preferably, the rate of the dropwise addition is 0.1-0.45 mL / min, for example, 0.25 mL / min.

[0065] In step S2-1, the heating temperature is preferably 80-100°C, for example, 90°C.

[0066] In step S2-1, the heating time is preferably 20-24 hours.

[0067] In step S2-2, the sintering temperature is preferably 200-400°C, for example, 300°C.

[0068] In step S2-2, the sintering time is preferably 2-6 h, for example 3 h.

[0069] In step S2-2, the sintering is preferably performed in a microwave oven.

[0070] In step S2-3, the carbonization temperature is preferably 500-850°C, for example 650°C.

[0071] Preferably, the heating rate to the carbonization temperature is 1-10°C / min, for example, 3°C / min.

[0072] In step S2-3, the carbonization time is preferably 10-20 h, for example 15 h.

[0073] In step S2-3, the carbonization is preferably performed in a tubular furnace.

[0074] In step S2-3, the carbonization is preferably carried out in an inert atmosphere. The inert atmosphere preferably includes an inert gas and / or nitrogen. The inert gas is preferably selected from one or more of helium, neon and argon. The nitrogen is, for example, high-purity nitrogen.

[0075] The present invention provides a composite silicon-carbon material, which is prepared by the above-mentioned method for preparing the composite silicon-carbon material.

[0076] The present invention provides an application of the composite silicon-carbon material as described above as a negative electrode material in a lithium-ion battery.

[0077] The present invention also provides a lithium ion battery, which comprises the composite silicon-carbon material as described above.

[0078] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0079] The reagents and raw materials used in the present invention are commercially available.

[0080] The positive and progressive effects of the present invention are:

[0081] The composite silicon-carbon material of the present invention uses graphene nanoribbons as a matrix, and sequentially coats a silicon layer and a graphene layer to obtain a sandwich structure, wherein the silicon layer is located between the graphene nanoribbon and another graphene layer, thereby constructing a three-dimensional silicon-carbon material. The composite silicon-carbon material has good electrical conductivity and good mechanical properties, and is conducive to improving the volume expansion defect of silicon. A lithium-ion battery using the composite silicon-carbon material can have excellent rate performance, first coulomb efficiency, capacity performance, and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0082] Figure 1 This is a rate performance test diagram of the lithium ion battery obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0083] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0084] Example 1

[0085] (1) Preparation of composite silicon-carbon materials

[0086] S0. Preparation of three-dimensional graphene nanoribbons:

[0087] Multi-walled carbon nanotubes (100 mg) were added to an oven-dried 250 mL round-bottom flask. The container was then transferred to a glove box and freshly distilled 1,2-dimethoxyethane (35 mL) was added, and 0.29 mL of liquid Na / K alloy was added. Ultrasonic dispersion was performed to obtain a dark green to red suspension. After ultrasonic treatment, the reaction mixture was vigorously stirred at room temperature for 3 days. The reaction suspension was then quenched by adding 1-iododecane (8.75 mmol) via syringe and stirred at room temperature for another day. Methanol was then added via syringe to quench any excess Na / K alloy and stirring was continued at room temperature for 10 min. The reaction mixture was filtered on a 0.45 μm pore size polytetrafluoroethylene membrane. The filter cake was washed with 100 mL of tetrahydrofuran, 100 mL of polyacrylate, 100 mL of water, 20 mL of polyacrylate, 20 mL of tetrahydrofuran, and 10 mL of ether. The filter cake was then dried under vacuum for 24 h (temperature: 90 °C) to obtain alkylated three-dimensional graphene nanoribbons (pore size: 16.8 nm, Dv50 particle size: 200 nm).

[0088] S1. Deposition of silicon:

[0089] Alkylated three-dimensional graphene nanoribbons were used as templates and sent into an atomic layer deposition (ALD) device (model: Beneq TFS200) with a flow rate of 80 mL / min of methylsilane gas. The operating temperature was 350°C for 40 h and the cycle was repeated 230 times. After the cycle was stopped, argon gas was used to purge the residual impurity gas. The cooling rate was controlled to be 15°C / min and the silicon-carbon precursor was obtained by cooling to room temperature.

[0090] S2, coated graphene layer:

[0091] S2-1. Add a silicon-carbon precursor and humic acid powder (analytical grade, purchased from Wanhua Chemical) in a mass ratio of 85:25 into deionized water and mix evenly to obtain a premix (solid-liquid ratio of 1:12), then dropwise add a 28wt% ammonia solution under stirring until the humic acid powder is completely dissolved; then heat to 90°C and evaporate the solvent at a constant temperature to evenly coat the surface of the silicon-carbon precursor with humic acid, to obtain a humic acid-coated silicon-carbon precursor, recorded as the first precursor;

[0092] S2-2, placing the first precursor in a microwave oven at 300° C. for 3 h, cooling and taking it out to obtain a second precursor;

[0093] S2-3. Then, the second precursor is placed in a tubular furnace (with an inert atmosphere), and the temperature is increased to a carbonization temperature of 650°C at a heating rate of 2°C / min, and heated at 650°C for 15 h to form a graphene layer in situ after thermal decomposition of the humic acid, thereby obtaining a composite silicon-carbon material.

[0094] (2) Preparation of button-type lithium-ion batteries

[0095] The composite silicon-carbon material prepared as the negative electrode material was mixed with a conductive agent (KS-6), a binder carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) at a mass ratio of 95.5:1.5:1.5:1.5 (a total of 100 g), added into 300 mL of water, and mixed evenly to obtain a negative electrode slurry. The negative electrode slurry was coated on a copper foil with a compaction density of 1.60 g / cm 3 , and used as the negative electrode after vacuum drying; lithium metal is used as the counter electrode; the solute in the electrolyte is LiPF6, the solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC) (mass ratio is 1:1), the concentration of the electrolyte is 1 mol / L; the separator is PE / PP / PE composite film, and it can be assembled into a button battery.

[0096] Example 2

[0097] The difference between this embodiment and embodiment 1 is that when preparing the composite silicon-carbon material, the working temperature in step S1 is 280° C., and the other conditions are the same as those in embodiment 1.

[0098] Example 3

[0099] The only difference between this embodiment and embodiment 1 is that when preparing the composite silicon-carbon material, the number of cycles in step S1 is 300 times, and the other conditions are the same as those in embodiment 1.

[0100] Example 4

[0101] The only difference between this embodiment and embodiment 1 is that when preparing the composite silicon-carbon material, the mass ratio of the silicon-carbon precursor to the humic acid powder in step S2-1 is 85:20, and the other conditions are the same as in embodiment 1.

[0102] Example 5

[0103] The only difference between this embodiment and embodiment 1 is that when preparing the composite silicon-carbon material, the mass ratio of the silicon-carbon precursor to the humic acid powder in step S2-1 is 80:25, and the other conditions are the same as in embodiment 1.

[0104] Example 6

[0105] The only difference between this embodiment and embodiment 1 is that when preparing the composite silicon-carbon material, the solid-liquid ratio in step S2-1 is 1:15, and the other conditions are the same as in embodiment 1.

[0106] Example 7

[0107] The only difference between this embodiment and embodiment 1 is that when preparing the composite silicon-carbon material, the carbonization temperature in step S2-3 is 750°C, and the other conditions are the same as in embodiment 1.

[0108] Example 8

[0109] The only difference between this embodiment and embodiment 1 is that when preparing the composite silicon-carbon material, the carbonization temperature in step S2-3 is 700°C, and the other conditions are the same as in embodiment 1.

[0110] Example 9

[0111] The only difference between this embodiment and embodiment 1 is that when preparing the composite silicon-carbon material, there is no step S0, and in step S1, two-dimensional graphene nanoribbons (purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., model number XFQ021) are used to replace three-dimensional graphene nanoribbons, and the other conditions are the same as in embodiment 1.

[0112] Example 10

[0113] The difference between this embodiment and embodiment 1 is that when preparing the composite silicon-carbon material, 1-iododecane is not used in step S0, and the other conditions are the same as those in embodiment 1.

[0114] Comparative Example 1

[0115] The difference between this comparative example and Example 1 is that: no composite silicon-carbon material is prepared; when preparing button-type lithium-ion batteries, pure silicon powder is directly used as the negative electrode material, and the other conditions are the same as Example 1.

[0116] Comparative Example 2

[0117] The difference between this comparative example and Example 1 is that when preparing the composite silicon-carbon material, only step S0 is included; when preparing the button-type lithium-ion battery, the alkylated three-dimensional graphene nanoribbon prepared in step S0 is used as the negative electrode material, and the other conditions are the same as in Example 1.

[0118] Comparative Example 3

[0119] The difference between this comparative example and Example 1 is that: when preparing the composite silicon-carbon material, steps S0 and S1 are omitted; in step S2, pure silicon powder and humic acid powder are directly mixed to obtain silicon powder coated with a graphene layer, which is used as a negative electrode material in a button-type lithium-ion battery; the other conditions are the same as in Example 1.

[0120] Comparative Example 4

[0121] The difference between this comparative example and Example 1 is that: when preparing the composite silicon-carbon material, there is no step S2; when preparing the button-type lithium-ion battery, the silicon-carbon precursor (graphene nanoribbon simply coated with a silicon layer) obtained in step S1 is directly used as the negative electrode material; the other conditions are the same as in Example 1.

[0122] Effect Example 1

[0123] The negative electrode materials obtained in Examples 1-10 and Comparative Examples 1-4 were tested for element content, conductivity, pore size and charge transfer internal resistance. The specific test methods are as follows:

[0124] (1) Element content

[0125] The element content is tested by XRF method:

[0126] First, the obtained negative electrode material was pre-treated by microwave digestion. 2±0.05g of stearic acid and 6±0.5g of the sample to be tested were mixed and ground, and then pressed into tablets. Then, the test was carried out in the Avio™ 200 equipment under the test condition of air pressure greater than 2MPa.

[0127] (2) Conductivity

[0128] The conductivity was measured at room temperature using an Orion Star™ A212 conductivity benchtop meter.

[0129] (3) Aperture

[0130] The pore size was measured using a POROLUX Cito instrument.

[0131] (4) Charge transfer internal resistance

[0132] The charge transfer resistance was measured by the Wuhan Landian Xinwei 5v / 10mA battery tester using the electrochemical impedance spectroscopy method (compacted density is 1.65g / cm 3 )get.

[0133] The above test results are shown in Table 1.

[0134] Effect Example 2

[0135] The lithium ion batteries prepared in Examples 1-10 and Comparative Examples 1-4 were subjected to the following performance tests using a Wuhan Blue Power Xinwei 5v / 10mA battery tester:

[0136] (1) First discharge specific capacity and first coulombic efficiency

[0137] The test method for the first discharge specific capacity is: charge to 2V at 0.1C constant current, discharge to 5mV at 0.1C constant current, and the capacity obtained is the first discharge specific capacity;

[0138] The test method for the first charge specific capacity is: discharge at a constant current of 0.1C to 5mV, and the capacity obtained at 0.1C is the first charge specific capacity;

[0139] Among them, the first coulombic efficiency = first discharge specific capacity / first charge specific capacity × 100%.

[0140] The results of the first discharge specific capacity and the first coulombic efficiency of the lithium ion batteries in Examples 1-10 and Comparative Examples 1-4 are shown in Table 2.

[0141] (2) Rate performance

[0142] At 25°C, the rate charge and discharge were carried out at a rate of 0.1C-2C, and the charging voltage was limited to 0.005-2V. At a charge rate of 0.1C current density, the rate performance (within 50 cycles) was tested at discharge rates of 0.1C, 0.2C, 0.5C, 1C, 2C and 3C.

[0143] The rate performance test diagram of the lithium ion battery in Example 1 is as follows: Figure 1 The rate performance test data of Example 1 and Comparative Examples 1-4 are shown in Table 3.

[0144] (3) Cycle performance

[0145] At 25°C, the cycle charge and discharge was carried out at a rate of 0.1C, and the charging voltage was limited to 0.005-2V. The cycle performance (within 200 cycles) was tested at a current density of 0.1C.

[0146] Among them, 200 cycle capacity retention rate = 200 cycle capacity at 0.1C rate / first discharge specific capacity × 100%.

[0147] The results of 200 cycle capacity retention rates of the lithium ion batteries in Examples 1-10 and Comparative Examples 1-4 are shown in Table 2.

[0148]

[0149]

[0150]

[0151] Note: “ / ” in Table 1 means that the condition parameter is not involved in the specific experiment.

[0152] According to Table 1, Table 2 and Table 3, the silicon content of the composite silicon-carbon material prepared in Examples 1-10 of the present invention can reach 28.9%-32.7%, and the electrical conductivity can reach (0.879-2.417)×10 3S / m, the pore size can reach 18.7-22.8 nm, and the charge transfer internal resistance can reach 38.9-67.8 Ω. The lithium-ion battery obtained by using the composite silicon-carbon material as the negative electrode material has excellent first coulombic efficiency and cycle performance, and takes into account excellent capacity performance and rate performance. Specifically, the first coulombic efficiency of the lithium-ion battery can reach more than 92%, or even more than 95%; the capacity retention rate after 200 cycles can reach more than 78%, or even more than 84%; the first discharge specific capacity can reach more than 1700 mAh / g, and the capacity after 200 cycles at a rate of 0.1C can reach more than 1350 mAh / g.

[0153] The present invention particularly designs a composite silicon-carbon material having a sandwich structure of graphene nanoribbons coated with silicon layers and graphene layers in sequence, so that the obtained lithium-ion battery can achieve excellent first coulombic efficiency, cycle performance, capacity performance and rate performance. However, the lithium-ion battery using pure silicon powder, alkylated three-dimensional graphene nanoribbons, silicon powder coated with graphene layers or graphene nanoribbons simply coated with silicon layers as negative electrode materials in the comparative examples cannot achieve the above-mentioned excellent performance. This may be because the unique mechanical properties of the inner and outer carbon layers in the composite silicon-carbon material of the outer carbon layer-silicon layer-inner carbon layer structure of the present invention fully alleviate the volume expansion of silicon, and the unique structure of the inner and outer carbon layers significantly improves the electrical conductivity of the silicon material, and at the same time has obvious results in improving the rate performance and cycle performance.

[0154] Compared with Example 1, pure silicon powder is directly used as the negative electrode material in Comparative Example 1. Although the obtained lithium-ion battery has high initial discharge specific capacity and 200 cycle capacity at a rate of 0.1C, and has excellent capacity performance, the initial coulombic efficiency, 200 cycle capacity retention rate and rate performance are greatly reduced, and it is impossible to take into account the excellent rate performance, initial coulombic efficiency and cycle performance.

[0155] Compared with Example 1, in Comparative Example 2, alkylated three-dimensional graphene nanoribbons are directly used as the negative electrode material, and the 200 cycle capacity retention rate, first coulombic efficiency and rate performance of the obtained lithium-ion battery are poor, and the first discharge specific capacity and the 200 cycle capacity at a rate of 0.1C are significantly deteriorated.

[0156] Compared with Example 1, in Comparative Example 3, silicon powder coated with a graphene layer is used as the negative electrode material. Although the first discharge specific capacity and the 200 cycle capacity at a rate of 0.1C of the obtained lithium-ion battery are relatively excellent, and have excellent capacity performance, the first coulombic efficiency and the 200 cycle capacity retention rate are significantly reduced, and the rate performance is poor, and it is impossible to take into account the excellent rate performance, the first coulombic efficiency and the cycle performance.

[0157] Compared with Example 1, Comparative Example 4 uses graphene nanoribbons simply coated with a silicon layer as the negative electrode material. Although the first discharge specific capacity and 200 cycle capacity at a rate of 0.1C of the obtained lithium-ion battery are relatively excellent, the first coulombic efficiency and 200 cycle capacity retention rate are significantly reduced, the rate performance is poor, and it is impossible to achieve the above-mentioned performance.

[0158] Compared with Example 1, the conventional two-dimensional graphene nanoribbons are used in Example 9, and the charge transfer internal resistance of the obtained silicon-carbon negative electrode material is improved, and the capacity performance, cycle performance and first coulombic efficiency of the obtained lithium-ion battery are all reduced. This may be because the three-dimensional graphene nanoribbons in Example 1 are conducive to opening the distance in space and reducing agglomeration, so the advantages of the composite silicon-carbon material can be fully utilized.

[0159] Compared with Example 1, Example 10 uses non-functionalized three-dimensional graphene nanoribbons, and the charge transfer internal resistance of the obtained silicon-carbon negative electrode material is improved, and the capacity performance, cycle performance and first coulombic efficiency of the obtained lithium-ion battery are all reduced. This may be because when functionalized three-dimensional graphene nanoribbons such as alkylated three-dimensional graphene nanoribbons are used in Example 1, it can further avoid the agglomeration of nanoribbons, thereby giving full play to the spatial advantages of three-dimensional graphene nanoribbons. Further, alkylated three-dimensional graphene nanoribbons can better give full play to the role of skeleton support, enhance conductivity, increase lithium ion transmission pathways, and reduce volume expansion, thereby further improving the capacity performance, cycle performance and first coulombic efficiency of the lithium-ion battery.

[0160] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A composite silicon-carbon material, characterized in that: The invention comprises a sandwich structure, wherein the sandwich structure comprises a graphene nanoribbon which is sequentially coated with a silicon layer and a graphene layer.

2. The composite silicon-carbon material according to claim 1, characterized in that: The sandwich structure satisfies one or more of the following conditions ac: a. The mass ratio of the graphene nanoribbon to the silicon layer is (1-3):1, for example, 1.7:1; b. The mass ratio of the graphene layer to the silicon layer is 1:(1-3), for example, 1:2; c. The graphene nanoribbon includes two-dimensional graphene nanoribbon and / or three-dimensional graphene nanoribbon, for example, three-dimensional graphene nanoribbon; wherein the three-dimensional graphene nanoribbon is preferably a functionalized three-dimensional graphene nanoribbon, and the functionalized three-dimensional graphene nanoribbon is, for example, an alkylated three-dimensional graphene nanoribbon.

3. The composite silicon-carbon material according to claim 1, characterized in that: The composite silicon-carbon material satisfies one or more of the following conditions: a. The silicon content of the composite silicon-carbon material is 25%-35%, preferably 28%-33%, for example, 28.9%, 29.6%, 29.8%, 30.4%, 30.5%, 31.8%, 30.8%, 32.4% or 32.7%; b. The carbon content of the composite silicon-carbon material is 60%-70%, preferably 63%-69%, for example, 63.7%, 63.8%, 64.2%, 64.9%, 65.7%, 66.5%, 66.7%, 67.2% or 68.2%; c. The oxygen content of the composite silicon-carbon material is 2%-5%, preferably 2.3%-4.7%, for example, 2.3%, 2.5%, 2.7%, 3.1%, 3.2%, 3.9%, 4.4% or 4.7%; d. The Dv50 particle size of the composite silicon-carbon material is 250-400 nm, preferably 288-352 nm, for example, 288 nm, 298 nm, 306 nm, 312 nm, 327 nm, 330 nm, 331 nm or 352 nm; e. The electrical conductivity of the composite silicon-carbon material is (0.8-2.5)×10 3 S / m, preferably (1.9-2.5)×10 3 S / m, for example, is 0.879×10 3 S / m, 1.897×10 3 S / m, 1.985×10 3 S / m, 2.089×10 3 S / m, 2.112×10 3 S / m, 2.217×10 3 S / m, 2.314×10 3 S / m, 2.417×10 3 S / m or 2.451×10 3 S / m; f. The pore size of the composite silicon-carbon material is 15-25 nm, preferably 18-22 nm, for example, 18.7 nm, 18.9 nm, 19.3 nm, 19.7 nm, 20.8 nm, 21.7 nm or 21.8 nm; g. The charge transfer internal resistance of the composite silicon-carbon material is 35-70 Ω, preferably 35-50 Ω, and more preferably 38-46 Ω, for example, 38.9 Ω, 39.7 Ω, 41.2 Ω, 42.8 Ω, 43.9 Ω, 44.7 Ω, 45.1 Ω or 67.8 Ω.

4. A method for preparing a composite silicon-carbon material, characterized in that: It includes the following steps: S1, depositing silicon on the graphene nanoribbon to obtain a silicon-carbon precursor; S2. Coating a graphene layer on the silicon-carbon precursor.

5. The method for preparing the composite silicon-carbon material according to claim 4, characterized in that: The graphene nanoribbon includes a three-dimensional graphene nanoribbon and / or a two-dimensional graphene nanoribbon, for example, a three-dimensional graphene nanoribbon; Wherein, the three-dimensional graphene nanoribbon is preferably a functionalized three-dimensional graphene nanoribbon, and the functionalized three-dimensional graphene nanoribbon is, for example, an alkylated three-dimensional graphene nanoribbon; Wherein, the pore size of the three-dimensional graphene nanoribbon is preferably 13.6-19.8 nm, for example, 16.8 nm; Wherein, the Dv50 particle size of the three-dimensional graphene nanoribbon is preferably 150-280 nm, for example, 200 nm; Wherein, the method for preparing the three-dimensional graphene nanoribbon preferably comprises the following steps: The mixture of carbon nanotubes, stabilizer and chain opener is subjected to a first reaction to obtain a reaction material; the reaction material is washed and dried to obtain the carbon nanotubes; wherein the carbon nanotubes include multi-walled carbon nanotubes; Preferably, the content of the multi-walled carbon nanotubes is greater than 50%, where the percentage is the mass percentage of the carbon nanotubes; Preferably, the carbon nanotubes further include single-walled carbon nanotubes; Preferably, the stabilizer is 1,2-dimethoxyethane; Preferably, the chain opening agent is a Na / K alloy; Preferably, after obtaining the reaction material, the method further comprises adding the reaction material to a functionalizing agent for a second reaction; wherein the functionalizing agent is preferably a halogenated alkane; Further preferably, the halogenated alkane is an iodinated alkane, for example, 1-iodinated alkane; the number of C atoms in the 1-iodinated alkane is preferably between 5 and 16; the 1-iodinated alkane is for example 1-iododecane; Preferably, the washing agent is one or more of methanol, tetrahydrofuran, polyacrylate, water and ether; Preferably, the method for preparing the mixture comprises the following steps: adding a stabilizer to the carbon nanotubes, and then adding a chain opening agent; Preferably, the preparation of the three-dimensional graphene nanoribbons is carried out in a glove box.

6. The method for preparing the composite silicon-carbon material according to claim 4, characterized in that: The method for depositing silicon is an atomic layer deposition method; the atomic layer deposition method comprises the following steps: Performing atomic layer deposition on the graphene nanoribbon using a silicon source gas; Preferably, the silicon source gas is silane; the silane preferably includes one or more of tetraethoxysilane, methylsilane and ethylsilane; Preferably, the flow rate of the silicon source gas is 50-100 mL / min, for example, 80 mL / min; Preferably, the working temperature of the atomic layer deposition is 200-400°C, for example, 350°C; preferably, the working duration of the atomic layer deposition is 32-48h, for example, 40h; preferably, the number of cycles of the atomic layer deposition is 200-400 times, for example, 230 times; Wherein, after the atomic layer deposition, the steps of purging with an inert gas and cooling are also included; The cooling rate of the cooling is preferably 10-30°C / min, for example 15°C / min.

7. The method for preparing the composite silicon-carbon material according to claim 4, characterized in that: The method for coating a graphene layer on the silicon-carbon precursor comprises the following steps: S2-1, heating the premix to remove the solvent, thereby obtaining a humic acid-coated silicon-carbon precursor, wherein the premix comprises the silicon-carbon precursor, humic acid and a solvent; S2-2, sintering the humic acid-coated silicon-carbon precursor; S2-3, carbonization, in-situ formation of graphene layers after thermal decomposition of humic acid; Wherein, in step S2-1, the humic acid is preferably humic acid powder; Wherein, in step S2-1, the mass ratio of the silicon-carbon precursor to the humic acid is preferably (80-90): (20-30), for example, 85:25; Wherein, in step S2-1, the solid-liquid ratio of the premix is ​​preferably 1:(10-15), for example, 1:12; Wherein, in step S2-1, the method for preparing the premix preferably comprises: adding the silicon-carbon precursor and humic acid into water and mixing them, and adding an ammonia solution under stirring conditions; Wherein, the mass concentration of the ammonia solution is preferably 10%-30%, for example, 28%; The method of adding the ammonia solution is preferably dropwise addition; preferably, the rate of the dropwise addition is 0.1-0.45 mL / min, for example, 0.25 mL / min; Wherein, in step S2-1, the heating temperature is preferably 80-100°C, for example, 90°C; the heating time is preferably 20-24h; Wherein, in step S2-2, the sintering temperature is preferably 200-400°C, for example, 300°C; the sintering time is preferably 2-6 h, for example, 3 h; and the sintering is preferably performed in a microwave oven; Wherein, in step S2-3, the carbonization temperature is preferably 500-850°C, for example, 650°C; preferably, the heating rate to the carbonization temperature is 1-10°C / min, for example, 3°C / min; the carbonization time is preferably 10-20 h, for example, 15 h; the carbonization is preferably carried out in a tubular furnace; Among them, in step S2-3, the carbonization is preferably carried out in an inert atmosphere; the inert atmosphere preferably includes an inert gas and / or nitrogen; the inert gas is preferably selected from one or more of helium, neon and argon; the nitrogen is, for example, high-purity nitrogen.

8. A composite silicon-carbon material, characterized in that: The composite silicon-carbon material is prepared by the method for preparing the composite silicon-carbon material as described in any one of claims 4 to 7.

9. Use of the composite silicon-carbon material as claimed in any one of claims 1 to 3 and 8 as a negative electrode material in a lithium-ion battery.

10. A lithium ion battery, characterized in that: It comprises the composite silicon-carbon material as described in any one of claims 1-3 and 8.

Citation Information

Cited By

  • Silicon-carbon negative electrode material utilizing atomic layer deposition and preparation method of silicon-carbon negative electrode material

    CN120432511A

  • Silicon-carbon composite material as well as preparation method and application thereof

    CN121023470A